Analisis kebijakan Moneter di Negara Mayoritas Muslim: Tunisia. - Nining Wahyuningsih; Putri Noviah Fatmawati (Pustaka Peradaban, 2024)
This research aims to analyze the monetary policy of Tunisia, a country with a Muslim-majority population, from both conventional and Islamic perspectives. Monetary policy, under the responsibility of the Central Bank, seeks to maintain currency stability and ensure overall economic strength. Islamic monetary policy specifically incorporates principles such as the prohibition of usury (riba), currency stability, the avoidance of excessive speculation, promoting productive financing, distributive justice, inflation control, and transparency. Tunisia, with its majority Muslim population, provides an interesting case for examining how Islamic principles are reflected—or not—in its monetary policy. This study employs a descriptive qualitative methodology, utilizing secondary data from library research, including websites and scientific journal articles. The findings show that Tunisia's monetary policy has a significant impact on economic indicators such as price stability, currency value, and overall economic growth, contributing to benefits like increased employment, higher purchasing power, improved investment levels, and sustainable economic prosperity. Key tools include interest rates, open market operations, reserve requirements, foreign currency interventions, selective credit policies, and macroprudential regulations.